FORMATION OF A HEALTHY LIFESTYLE AMONG STUDENTS OF THE DIRECTION OF MILITARY EDUCATION UP TO THE DRAFT - А. А. Mukhidinov (Journal Park Publishing, 2023)
For a citizen of independent Uzbekistan, for the younger generation entering an independent life, patriotism means loyalty to the ideas of national independence, preservation and enhancement of the independence of the Motherland. patriotism is a direct continuation of the creative work of our ancestors to develop our people and move it forward. To love this dear homeland means to preserve it - patriotism. In this article, the issue of the formation of a healthy lifestyle among students of the pre-conscription direction of military education is scientifically investigated.
Keywords: military education, patriotism, health, healthy lifestyle, society, Information culture, education, innovation.